2022
DOI: 10.26434/chemrxiv-2022-v2k12
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non aqueous Li-mediated nitrogen reduction: Taking control of potentials

Abstract: The performance of the Li-mediated ammonia synthesis has progressed dramatically since its recent reintroduction. However, fundamental understanding of this reaction is slower paced, due to the many uncontrolled variables influencing it. To address this, we developed a true non-aqueous LiFePO4 reference electrode, providing both a redox anchor from which to measure potentials against, and estimates of energy efficiency loss sources. We demonstrate its stable electrochemical potential in operation using differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…24 Quantitative electrochemical measurements of suppression of Li plating will be possible given recent developments of more accurate reference electrodes for the Li-mediated system. 25,26 Our own XPS results are remarkably similar to those of Li et al, as shown in Figure 3a-d: increasing water generally shifts the peaks away from those corresponding to LiClO n under dry conditions (i.e., 533 eV for O 1s and 56.9 eV for Li 1 s) to those corresponding to toward Li 2 O under moist conditions (i.e., 531.5 eV for O 1s and 55.3 eV for Li 1 s. Our results suggest that the replacement of LiClO n , LiCl, and related species with nonchlorinated species such as Li 2 O, consistent with earlier reports from the battery literature on the effect of trace H 2 O on the SEI. 4 Increasing the water concentration beyond the optimum appears to increase surface Li atomic concentration (46% to 54%) and decrease O concentration slightly (41% to 34%), which could indicate increased Li 2 O formation, as shown in Figure 3d.…”
mentioning
confidence: 99%
“…24 Quantitative electrochemical measurements of suppression of Li plating will be possible given recent developments of more accurate reference electrodes for the Li-mediated system. 25,26 Our own XPS results are remarkably similar to those of Li et al, as shown in Figure 3a-d: increasing water generally shifts the peaks away from those corresponding to LiClO n under dry conditions (i.e., 533 eV for O 1s and 56.9 eV for Li 1 s) to those corresponding to toward Li 2 O under moist conditions (i.e., 531.5 eV for O 1s and 55.3 eV for Li 1 s. Our results suggest that the replacement of LiClO n , LiCl, and related species with nonchlorinated species such as Li 2 O, consistent with earlier reports from the battery literature on the effect of trace H 2 O on the SEI. 4 Increasing the water concentration beyond the optimum appears to increase surface Li atomic concentration (46% to 54%) and decrease O concentration slightly (41% to 34%), which could indicate increased Li 2 O formation, as shown in Figure 3d.…”
mentioning
confidence: 99%
“…Methods. LiMEAS experiments were conducted using a onecompartment cell with a Cu cathode, Pt mesh anode, and Li 0.5 FePO 4 reference electrode, 37,38 all submerged in 16 mL of electrolyte solution. 5% H 2 in N 2 gas was bubbled through the electrolyte at 5 mL•min −1 for 20 min prior to current passage and continued to flow while current was applied.…”
mentioning
confidence: 99%